PENINGKATAN ILMU IOT DALAM PENGATURAN UDARA BERSIH DI KOTA MEDAN - Togar Timoteus (Jurnal Abdi Ilmu, 2021)
This article reports an analysis of Control IOT to Clean Air Act enforcements by Arduino and the separately and in relative dependence with one another. The results show that federal implementation is not easily understood by examining parts of a federal structure; rather, more insight comes by examining implementation as a system. For clean air, national and subnational outputs were inertial, interdependent, and linked to both vertical and horizontal influences In this paper described about air population at room, Several studies have examined implementation determinants for parts of a indonesia policy medic, either national or subnational. However, no study treats federal implementation comprehensively as a single system by examining both national and subnational outputs in mutual interdependence.. The implication is that federal structures are adaptive entities that provide greater democratic representation than other administrative forms.